Knowledge Base for Teaching and Sustainability. A Study about Curricular Environmentalization on Pedagogy Course of State University of West Paraná - Rechia Vasconcellos da Rosa, Talita; Malacarne, Vilmar (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2016)
This work presents the results of the document analysis of the Pedagogy course of State University of West, campus of Cascavel, Paraná, Brazil. The purpose of this article is to show how is the curriculum environmentalization process of this course through the analysis of the disciplines curriculum, using as parameters the Curriculum Environmentalization of Higher Education (ACES) Network indicators, the National Curriculum Guidelines for Environmental Education (DCNEA) and the National Environmental Education Policy (PNEA) as a basis for the seizure of sustainability content. The document analysis was performed through the techniques of the Bardin (2011) Content Analysis method in which the results indicated that the insertion of sustainability content on the curriculum of disciplines, from Pedagogy course, presents minimum principles of ACES Network and DCNEA, showing a fragile and incipient Environmental Education in teacher training. The data enabled to verify the pressing need to change the curricula for these professionals training to set up a formative path in line with education needs of the new generations committed to the sustainable development in Brazil.